High rates of hypertension, diabetes, elevated low-density lipoprotein cholesterol, and cardiovascular disease risk factors in HIV-infected patients in Malawi. (14th January 2018) - Mathabire Rücker, Sekai C.; Tayea, Alia; Bitilinyu-Bangoh, Joseph; Bermúdez-Aza, Elkin H.; Salumu, Leon; Quiles, Isabel Amoros; Szumilin, Elisabeth; Chirwa, Zengani; Rick, Fernanda; Maman, David
Abstract : Objectives: Data on cardiovascular disease risks among HIV-infected patients taking antiretroviral therapy (ART) over long periods of time are lacking in Sub-Saharan Africa. Methods: A cross-sectional study was conducted in Chiradzulu, Malawi from December 2015 to June 2016. HIV-infected persons on ART for more than 10 years (patients) and HIV-negative individuals (controls) from selected clinics participated. Following informed consent, a standardized questionnaire, clinical and laboratory examinations were performed. The prevalence of cardiovascular disease risk factors was calculated and stratified by age group. Results: Overall, 379 HIV-infected patients and 356 controls participated. Median time on ART among patients was 11.6 years (interquartile range 10.6–12.4).Within the 30–44, 45–59, and at least 60-year age groups, respectively, the prevalence of hypertension was 10.8, 20.4, and 44.7% among patients and 6.1, 25.8, and 42.9% among controls. Hypertension was previously undiagnosed in 60.3% patients and 37.0% controls with elevated blood pressure. The prevalence of diabetes within the respective age groups was 5.0, 6.4, and 13.2% among patients, and 3.4, 4.2, and 1.7% among controls. HIV-infected patients were more likely to have an glycated hemoglobin at least 6.0% (adjusted odds ratio 1.9; 95% confidence interval 1.1–3.2, P  = 0.02). Prevalence of low-density lipoprotein cholesterol more than 130 mg/dl within the respective age groups was 8.0, 15.4, and 23.7% among patients and 1.8, 12.5, and 11.8% among controls. Conclusion: Noncommunicable diseases were a significant burden in Malawi, with high prevalence of hypercholesterolemia in all survey participants and an especially acute diabetes burden among older HIV infected. Hypertension screening and treatment services are needed among identified high-risk groups to cover unmet needs.